Muslim-Friendly Tourism Facilities and Visiting Intention in Halal Tourism: The Mediating Role of Halal Certification Benefits - Evi Febriana; Bethani Suryawardani; Ganjar Mohamad Disastra (Journal of Digital Marketing and Communication, 2026)
Driven by the rising demand for services aligned with Islamic values, halal tourism emerged as a critical segment in Indonesia's hospitality industry. This shift forced destinations to recalibrate how they operationalized religious comfort and structural compliance for Muslim travelers. While existing literature heavily explored Muslim travel behavior through the lenses of destination attributes, religiosity, and perceived value, empirical insights remained sparse regarding how tangible faith-based facilities interacted with institutional trust signals such as halal certification to shape visiting intentions. To explore these dynamics, this study deployed a quantitative research design to evaluate the impact of Muslim-Friendly Tourism Facilities (MFF) on Visiting Intention (MVI), specifically examining the mediating role of Perceived Benefits of Halal Certification (PBH). Utilizing a purposive sampling approach, data were gathered from 250 Muslim respondents and subsequently analyzed via PLS-SEM using SmartPLS 4. The empirical findings substantiated that faith-based amenities shaped visitor behavior through both direct pathways and indirect mechanisms through certification perceptions. Given that the direct link between facilities and intentions remained statistically meaningful alongside the significant indirect path, the perceived benefits of halal certification functioned strictly as a partial mediator.